2015
DOI: 10.3892/mmr.2015.4537
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-566 modulates vascular endothelial growth factor by targeting Von Hippel-Landau in human glioblastoma in vitro and in vivo

Abstract: MicroRNAs (miRNAs) are able to function as either oncogenes or tumor suppressor genes in tumorigenesis, and have been proposed as novel targets for anticancer treatment. It has previously been suggested that miRNAs have important roles in the initiation and progression of glioblastoma; however, the effects of miR‑566 in glioblastoma are currently unclear. The present study aimed to demonstrate that miR-566 can modulate vascular endothelial growth factor (VEGF) by targeting Von Hippel‑Lindau (VHL) in glioblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Glioma, particularly glioblastoma, has a poor prognosis (4,13). It is one of the most common highly vascularized malignant tumors of the CNS, with a ≤12-month median survival period (5,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioma, particularly glioblastoma, has a poor prognosis (4,13). It is one of the most common highly vascularized malignant tumors of the CNS, with a ≤12-month median survival period (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, glioma is the most common type of malignant tumor of the brain and central nervous system, characterized by rapid progression, aggressive behavior, frequent recurrence and poor prognosis (1,2). Despite advances in diagnosis and treatment, frequent recurrence and a low cure rate of glioma remain due to the rapid proliferation and high invasiveness of this disease, particularly for glioblastoma multiforme patients (3,4). It is in essence a genetic disease with overexpression of oncogenes and deletions or mutations of tumor-suppressor genes, which lead to the uncontrolled proliferation of cancer cells (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in this GSC line, we observed a modulation of VEGF mRNA by hypoxia that was not paralleled by a modulation of VEGF protein expression (compare Figure 1C with Figure 2C). Even if we did not investigate into that, we think that such a discrepancy might be due to: (i) a post-transcriptional control by miRNA that prevent expression of VEGF from mRNA either directly as in the case of miR-16 [49] or indirectly by targeting VHL protein as in the case of miR-566 [50]; (ii) the intratumoral heterogeneity of line #83 that contains tumor cells with different metabolic behavior that when sub-cloned gave rise to cell lines belonging to separate metabolic clusters [51]. In the latter case, this heterogeneity might reflect in opposite trends of VEGF protein expression showing, on average, no significant increase.…”
Section: Discussionmentioning
confidence: 98%
“…A prior study suggested that tuberous sclerosis complex protein 1 expression is affected by VHL gene alterations and HIF-1α expression in renal cell carcinoma (23). It was also demonstrated that miR-566 regulates vascular endothelial growth factor (VEGF) by targeting VHL in human glioblastoma in vitro and in vivo (24). Another study suggested that hsa-miR-331-3p downregulates VHL expression in hepatocellular carcinoma cell lines by targeting its 3'-UTR (25), and that miR-101 targets VHL to promote HIF-1α-mediated apoptosis and cell cycle arrest (26).…”
Section: Discussionmentioning
confidence: 99%